Cuticular reticulation replicates the pattern of epidermal cells in lowermost Cambrian scalidophoran worms. Issue 1926 (13th May 2020) - Wang, Deng; Vannier, Jean; Yang, Xiao-guang; Sun, Jie; Sun, Yi-fei; Hao, Wen-jing; Tang, Qing-qin; Liu, Ping; Han, Jian
Abstract : The cuticle of ecdysozoans (Panarthropoda, Scalidophora, Nematoida) is secreted by underlying epidermal cells and renewed via ecdysis. We explore here the relationship between epidermis and external cuticular ornament in stem-group scalidophorans from the early Cambrian of China (Kuanchuanpu Formation; ca 535 Ma) that had two types of microscopic polygonal cuticular networks with either straight or microfolded boundaries. Detailed comparisons with modern scalidophorans (priapulids) indicate that these networks faithfully replicate the cell boundaries of the epidermis. This suggests that the cuticle of early scalidophorans formed through the fusion between patches of extracellular material secreted by epidermal cells, as observed in various groups of present-day ecdysozoans, including arthropods. Key genetic, biochemical and mechanical processes associated with ecdysis and cuticle formation seem to have appeared very early (at least not later than 535 Ma) in the evolution of ecdysozoans. Microfolded reticulation is likely to be a mechanical response to absorbing contraction exerted by underlying muscles. The polygonal reticulation in early and extant ecdysozoans is clearly a by-product of the epidermal cell pavement and interacted with the sedimentary environment.